Evaluating Italian public hospital efficiency using bootstrap DEA and CART. (1st January 2013) - De Nicola, Arianna; Gitto, Simone; Mancuso, Paolo
We estimate the efficiency of 390 Italian public hospitals in 2007, using the bias-corrected data envelopment analysis (DEA) estimates. Then, classification and regression tree (CART) methodology, based on the bias-corrected DEA results, is used to investigate the relationships between health efficiency of the hospitals, physicians, nurses, beds and discharges. The results show that the main factors affecting health efficiency of the Italian public hospitals are the number of beds and the number of discharges. Finally, the paper shows that a process of bed downsizing may result in a deterioration of health efficiency of the Italian public hospital.